Method for preparing gas separation composite membrane through polymerization by adding carboxymethyl chitosan

By pretreatment, nanostructure regulation, thermal annealing and surface modification of the support film, the problem of poor bonding between the support film and the separation layer is solved, and the efficient stability and long life of the gas separation composite film is achieved.

CN120325096APending Publication Date: 2025-07-18HENAN INST OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510613994.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

During long-term use of traditional composite films, due to the inadequate bond between the support film and the separation layer, the gas separation efficiency is reduced and the service life is shortened.

Method used

The support film was subjected to ethanol solution cleaning, oxygen plasma treatment and 3-aminopropyltriethoxysilane solution soaking treatment to enhance the surface activity and polarity of the support film; the nanostructure formation was guided by ZSM-5 molecular sieve as a template, and the interface was carried out in-situ polymerization reaction; thermal annealing and glutaraldehyde cross-linking treatment enhanced the structural stability of the film; polyimide solution was added dropwise to the surface and plasma treatment was performed to introduce functional groups.

Benefits of technology

The bonding force between the support film and the separation layer is improved, the gas separation performance and stability of the composite film is enhanced, the service life is extended, and the gas separation efficiency and selectivity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120325096A_ABST
    Figure CN120325096A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of separation composite membranes, and discloses a method for preparing a gas separation composite membrane through polymerization by adding carboxymethyl chitosan. Comprising the following steps: S1, pretreatment of a support membrane: sequentially carrying out cleaning treatment, oxygen plasma treatment and 3-aminopropyltriethoxysilane solution soaking treatment on a polysulfone, polyethersulfone or polyacrylonitrile support membrane; s2, solution preparation: preparing deionized water, carboxymethyl chitosan, piperazine, trimesoyl chloride and normal hexane, adding carboxymethyl chitosan and piperazine into the deionized water, and stirring until the carboxymethyl chitosan and piperazine are completely dissolved; the supporting membrane is subjected to ethanol solution cleaning, oxygen plasma treatment and 3-aminopropyltriethoxysilane solution soaking, a polar group is introduced through plasma treatment to improve the surface activity, and a coupling agent coating is formed through silane solution treatment, so that the binding force between the supporting membrane and a subsequent separation layer is effectively enhanced, and the composite membrane is more stable in structure; the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation composite membranes, and specifically to a method for preparing a gas separation composite membrane by adding carboxymethyl chitosan for polymerization. Background Art

[0002] In the field of gas separation, with the development of industry and the improvement of environmental protection requirements, efficient separation technologies have become increasingly crucial. Membrane separation technology has become a research and application hotspot due to its advantages such as simple process, good operation flexibility, and insignificant amplification effect. As the core, the performance of gas separation composite membranes directly affects the separation effect and application scope. As an important polymer raw material, carboxymethyl chitosan has gradually emerged in the preparation of gas separation composite membranes. Carboxymethyl chitosan is obtained by chemically modifying chitosan, and its structure and properties have unique changes, providing a new way to optimize the performance of gas separation composite membranes.

[0003] During the long-term use of traditional composite membranes, due to the weak bonding between the support membrane and the separation layer, the gas separation efficiency decreases, and the service life of the membrane is significantly shortened. Summary of the Invention

[0004] Aiming at the deficiencies of the existing technology, the present invention provides a method for preparing a gas separation composite membrane by adding carboxymethyl chitosan for polymerization, which solves the problem that during long-term use, due to the weak bonding between the support membrane and the separation layer, the gas separation efficiency decreases, and the service life of the membrane is significantly shortened.

[0005] To achieve the above objectives, the present invention is realized through the following technical solutions. A method for preparing a gas separation composite membrane by adding carboxymethyl chitosan for polymerization includes the following steps:

[0006] S1. Support membrane pretreatment: Sequentially perform cleaning treatment, oxygen plasma treatment, and immersion treatment with 3-aminopropyltriethoxysilane solution on a polysulfone, polyethersulfone, or polyacrylonitrile support membrane;

[0007] S2. Solution preparation: Prepare deionized water, carboxymethyl chitosan, piperazine, trimesoyl chloride, and n-hexane. Add carboxymethyl chitosan and piperazine to deionized water, stir until completely dissolved, make an aqueous phase mixed solution and let it stand. Dissolve trimesoyl chloride in n-hexane and stir to make an organic phase solution;

[0008] S3. Reaction system construction: Select ZSM-5 molecular sieve as a template and add it to the aqueous phase mixed solution, and stir to form a reaction system containing an aqueous phase and an organic phase;

[0009] S4. In-situ polymerization reaction: Lay the support membrane pretreated in step S1 flat in a petri dish, pour the organic phase solution prepared in step S2 to infiltrate it, and then pour the aqueous phase solution formed in step S3 onto the surface of the support membrane for interfacial in-situ polymerization reaction;

[0010] S5, Template Removal: Put the preliminary composite membrane obtained in step S4 into a muffle furnace for calcination to remove the ZSM-5 molecular sieve template, and take it out after natural cooling;

[0011] S6, Put the preliminary composite membrane processed in step S5 into a vacuum drying oven for thermal annealing treatment, soak it in an aqueous glutaraldehyde solution at room temperature for crosslinking, then rinse it with deionized water, and finally dry it;

[0012] S7, Surface Optimization: Drop polyimide solution at the center of the composite membrane processed in step S6, then put it into a drying oven for drying, and finally put it into a plasma device for treatment.

[0013] Through the above technical solutions: Through step S1, the impurities on the surface of the support membrane can be effectively removed, its surface activity and polarity can be improved, and the bonding force between the support membrane and the subsequent separation layer can be enhanced, laying a foundation for the preparation of a gas separation composite membrane with excellent performance;

[0014] Through step S2, a suitable reaction system can be provided for the subsequent in-situ polymerization reaction, enabling the polymerization reaction to proceed smoothly and ensuring the structure and performance of the composite membrane;

[0015] Through step S3, the special structure of the molecular sieve is used to guide the formation of nanostructures during the polymerization reaction, realizing the regulation of the nanostructures of the composite membrane, which helps to improve the gas separation performance and selectivity of the composite membrane;

[0016] Through step S4, an interfacial in-situ polymerization reaction is carried out to form a separation layer on the surface of the support membrane. This method can make the separation layer tightly combined with the support membrane, and by controlling the reaction conditions, the thickness and structure of the separation layer can be precisely controlled, thereby improving the gas separation efficiency and stability of the composite membrane;

[0017] Through step S5, a composite membrane with a specific nanoporous structure can be formed after removing the template. These pore structures are beneficial to the penetration and separation of gases, enabling the composite membrane to have good gas separation functions;

[0018] Through step S6, the thermal annealing treatment can make the molecular chain segments in the membrane rearrange regularly, improving the denseness of the membrane. The crosslinking treatment enhances the structural stability of the membrane, improves the mechanical properties and chemical stability of the composite membrane, and extends the service life of the composite membrane;

[0019] Through step S7, drop polyimide solution on the surface of the composite membrane and dry it, and then introduce functional groups through plasma treatment. The polyimide coating can fill the defects on the membrane surface, improving the selectivity of the membrane. The functional groups introduced by plasma treatment can improve the chemical properties of the membrane surface, enhance the anti-pollution performance and gas separation performance of the membrane, and further improve the overall performance of the composite membrane.

[0020] Preferably, in the step S1, the cleaning treatment includes soaking the support film in an ethanol solution for 20 - 40 minutes, then rinsing it with deionized water 2 - 4 times, 3 - 7 minutes each time, and then air-drying it in a dust-free environment for 0.5 - 1.5 hours. The oxygen plasma treatment includes placing the cleaned support film in a reaction chamber, setting the oxygen flow rate at 40 - 60 sccm, the pressure at 8 - 12 Pa, and the power at 80 - 120 W, and treating it for 8 - 12 minutes. The soaking treatment with 3-aminopropyltriethoxysilane solution includes soaking the support film in a 3-aminopropyltriethoxysilane solution with a mass fraction of 1.5% - 2.5%. The 3-aminopropyltriethoxysilane solution is a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1 - 5:1. Soak it at room temperature for 1.5 - 2.5 hours, take it out and rinse it with anhydrous ethanol 2 - 4 times, and dry it in a vacuum drying oven at 55 - 65 °C for 1.5 - 2.5 hours.

[0021] Preferably, in the step S2, according to the molar ratio of carboxymethyl chitosan to piperazine of 1.5 - 2.5:2.5 - 3.5, stir it at 250 - 350 r / min until completely dissolved, prepare an aqueous phase mixed solution with a mass fraction of 2.5% - 3.5% and let it stand for 25 - 35 minutes. Trimellitic acid chloride is dissolved in n-hexane and stirred at 180 - 220 r / min for 0.8 - 1.2 hours to prepare an organic phase solution with a mass fraction of 0.8% - 1.2%.

[0022] Preferably, in the step S3, the pore size of the ZSM-5 molecular sieve is 4 - 12 nm. Add it to the aqueous phase mixed solution according to the mass ratio of 0.8 - 1.2:5 to carboxymethyl chitosan, and continue to stir for 25 - 35 minutes to form a reaction system.

[0023] Preferably, in the step S4, pour the organic phase solution prepared in the step S2, soak it for 4 - 6 minutes, pour off the excess solution, and blot the residue with filter paper. Pour the aqueous phase solution formed in the step S3 onto the surface of the support film, and carry out an interfacial in-situ polymerization reaction at a temperature of 23 - 27 °C for 18 - 22 minutes.

[0024] Preferably, in the step S5, the muffle furnace is heated to 530 - 570 °C at a rate of 4 - 6 °C / min, calcined for 5 - 7 hours to remove the ZSM-5 molecular sieve template, and nitrogen is continuously introduced for protection during the process.

[0025] Preferably, in S6, the temperature of the vacuum drying oven is 75 - 85°C, the vacuum degree is -0.07 MPa to -0.09 MPa, for 3.5 - 4.5 hours to complete the thermal annealing treatment. The mass fraction of the glutaraldehyde aqueous solution is 0.8% - 1.2%, crosslinking is carried out at room temperature for 1.8 - 2.2 hours. After crosslinking, it is rinsed with deionized water 2 - 4 times, each time for 8 - 12 minutes, and finally placed in a vacuum drying oven at 45 - 55°C for drying for 1.8 - 2.2 hours.

[0026] Preferably, in S7, the solid content in the polyimide solution is 4.5% - 5.5%. When spin - coating is carried out by the spin - coating method, it is spin - coated at a speed of 900 - 1100 r / min for 25 - 35 seconds to form a coating with a thickness of about 0.4 - 0.6 μm. The coated composite film is placed in a drying oven at 75 - 85°C for drying for 0.8 - 1.2 hours. Then the composite film is placed in a plasma treatment device, and carbon tetrafluoride gas with a flow rate of 25 - 35 sccm is introduced. The reaction chamber pressure is set to 13 - 17 Pa and the power is 75 - 85 W, and it is treated for 7 - 9 minutes to introduce functional groups.

[0027] Preferably, in S1, after the support membrane is soaked and treated with 3 - aminopropyltriethoxysilane solution, the surface roughness of the support membrane is detected. If the surface roughness Ra does not meet 0.5 - 5 nanometers, the soaking treatment with 3 - aminopropyltriethoxysilane solution is repeated.

[0028] Preferably, in S7, after the functional groups are introduced by plasma treatment, X - ray photoelectron spectroscopy analysis is carried out on the surface of the composite film to detect the content and distribution of the functional groups, ensuring that the atomic percentage content of fluorine elements on the surface of the composite film is 5% - 15%, and the deviation of the distribution uniformity of the fluorine - containing groups on the film surface is less than 10%.

[0029] The present invention provides a method for preparing a gas - separation composite membrane by adding and polymerizing carboxymethyl chitosan.

[0030] It has the following beneficial effects:

[0031] 1. In the present invention, by cleaning the support membrane with an ethanol solution, oxygen plasma treatment, and soaking treatment with 3 - aminopropyltriethoxysilane solution, the ethanol cleaning removes surface oil and impurities, the plasma treatment introduces polar groups to improve surface activity, and the silane solution treatment forms a coupling agent coating. The three work together synergistically to effectively enhance the bonding force between the support membrane and the subsequent separation layer, making the composite membrane structure more stable and improving the service life.

[0032] 2. The present invention controls the molar ratio of carboxymethyl chitosan and piperazine, the stirring speed and the mass fraction of the solution, and rationally prepares the organic phase solution with a certain raw material ratio and stirring conditions to make the aqueous phase mixed solution uniform and stable. The precise preparation of the organic phase solution ensures the reaction activity and provides an ideal system for in-situ polymerization, which is conducive to forming a gas separation composite membrane with uniform structure and excellent performance, thereby improving the success rate and quality stability of the composite membrane preparation.

[0033] 3. The present invention selects ZSM-5 molecular sieve with a specific pore size as a template, adds an aqueous phase mixed solution in proportion and stirs it fully, and uses the special structure of the molecular sieve to guide the formation of nanostructures in the polymerization reaction, thereby achieving precise control of the size and distribution of nanopores in the composite membrane, thereby improving the screening ability and separation efficiency of the gas separation composite membrane for different gases.

[0034] 4. The present invention performs thermal annealing and glutaraldehyde cross-linking treatment on the preliminary composite membrane, and then rinses and dries it. Thermal annealing promotes the rearrangement of molecular segments in the membrane, eliminates internal stress, and improves the density of the membrane. Glutaraldehyde cross-linking forms a network structure and enhances the mechanical strength of the membrane. After cross-linking, it is rinsed to remove impurities and dried to consolidate the structure, thereby improving the mechanical strength, chemical stability and structural integrity of the composite membrane and extending the service life of the composite membrane in gas separation applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a schematic flow chart of a method for preparing a gas separation composite membrane by adding carboxymethyl chitosan for polymerization. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for preparing a gas separation composite membrane by adding carboxymethyl chitosan for polymerization, comprising the following steps:

[0038] S1. Support membrane pretreatment: the polysulfone, polyethersulfone or polyacrylonitrile support membrane is sequentially cleaned, treated with oxygen plasma and immersed in a 3-aminopropyltriethoxysilane solution;

[0039] S2. Solution preparation: Prepare deionized water, carboxymethyl chitosan, piperazine, trimesoyl chloride, and n-hexane. Add carboxymethyl chitosan and piperazine to deionized water, stir until completely dissolved to form an aqueous mixed solution and let it stand. Dissolve trimesoyl chloride in n-hexane and stir to form an organic phase solution;

[0040] S3. Reaction system construction: Select ZSM-5 zeolite as a template and add it to the aqueous mixed solution. After stirring, a reaction system containing an aqueous phase and an organic phase is formed;

[0041] S4. In-situ polymerization reaction: Lay the support membrane pretreated in step S1 flat in a petri dish, pour in the organic phase solution prepared in step S2 to soak it, and then pour the aqueous phase solution formed in step S3 on the surface of the support membrane to carry out an interfacial in-situ polymerization reaction;

[0042] S5. Template removal: Put the preliminary composite membrane obtained in step S4 into a muffle furnace for calcination to remove the ZSM-5 zeolite template, and take it out after natural cooling;

[0043] S6. Put the preliminary composite membrane treated in step S5 into a vacuum drying oven for heat annealing treatment, soak it in an aqueous glutaraldehyde solution for crosslinking at room temperature, then rinse it with deionized water, and finally dry it;

[0044] S7. Surface optimization: Drop a polyimide solution at the center of the composite membrane treated in step S6, then put it into a drying oven to dry, and finally put it into a plasma device for treatment.

[0045] Specifically, in step S1, by sequentially performing cleaning treatment, oxygen plasma treatment, and immersion treatment in a 3-aminopropyltriethoxysilane solution on a polysulfone, polyethersulfone, or polyacrylonitrile support membrane, impurities on the surface of the support membrane can be effectively removed, its surface activity and polarity can be improved, and the bonding force between the support membrane and the subsequent separation layer can be enhanced, solving the problem of poor compatibility between the support membrane and the separation layer, and laying a foundation for preparing a gas separation composite membrane with excellent performance;

[0046] In step S2, prepare various raw materials such as deionized water and carboxymethyl chitosan, and separately make an aqueous mixed solution and an organic phase solution, ensuring the uniformity and stability of the solution, providing a suitable reaction system for the subsequent in-situ polymerization reaction, enabling the polymerization reaction to proceed smoothly, and ensuring the structure and performance of the composite membrane;

[0047] In step S3, select ZSM-5 zeolite as a template and add it to the aqueous mixed solution. After stirring, a reaction system containing an aqueous phase and an organic phase is formed. Utilize the special structure of the zeolite to guide the formation of nanostructures during the polymerization reaction, realize the regulation of the nanostructure of the composite membrane, and contribute to improving the gas separation performance and selectivity of the composite membrane;

[0048] In step S4, the pretreated support membrane is successively infiltrated with an organic phase solution and an aqueous phase solution to carry out an interfacial in-situ polymerization reaction, forming a separation layer on the surface of the support membrane. This method can enable the separation layer to be tightly combined with the support membrane, and by controlling the reaction conditions, the thickness and structure of the separation layer can be precisely controlled, thereby improving the gas separation efficiency and stability of the composite membrane;

[0049] In step S5, the preliminary composite membrane is placed in a muffle furnace for calcination to remove the ZSM-5 molecular sieve template. After removing the template, a composite membrane with a specific nano-pore structure can be formed. These pore structures are beneficial to the penetration and separation of gases, enabling the composite membrane to have good gas separation performance and solving the problem that the residual template in the membrane structure affects the performance;

[0050] In step S6, the preliminary composite membrane is subjected to heat annealing treatment and glutaraldehyde cross-linking treatment, followed by rinsing and drying. The heat annealing treatment can rearrange and regularize the molecular chain segments in the membrane, improving the denseness of the membrane. The cross-linking treatment enhances the structural stability of the membrane, improves the mechanical properties and chemical stability of the composite membrane, and extends the service life of the composite membrane;

[0051] In step S7, a polyimide solution is dropped on the surface of the composite membrane and dried, and then functional groups are introduced by plasma treatment. The polyimide coating can fill the defects on the membrane surface and improve the selectivity of the membrane. The functional groups introduced by plasma treatment can improve the chemical properties of the membrane surface, enhance the anti-pollution performance and gas separation performance of the membrane, and further improve the overall performance of the composite membrane.

[0052] In S1, the cleaning treatment includes soaking the support membrane in an ethanol solution for 20 - 40 minutes, then rinsing it with deionized water 2 - 4 times, 3 - 7 minutes each time, and then air-drying it in a dust-free environment for 0.5 - 1.5 hours. The oxygen plasma treatment includes placing the cleaned support membrane in a reaction chamber, setting the oxygen flow rate at 40 - 60 sccm, the pressure at 8 - 12 Pa, the power at 80 - 120 W, and treating it for 8 - 12 minutes. The soaking treatment with 3-aminopropyltriethoxysilane solution includes soaking the support membrane in a 3-aminopropyltriethoxysilane solution with a mass fraction of 1.5% - 2.5%. The 3-aminopropyltriethoxysilane solution is a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1 - 5:1. Soak it at room temperature for 1.5 - 2.5 hours, take it out and rinse it with anhydrous ethanol 2 - 4 times, and dry it in a vacuum drying oven at 55 - 65 °C for 1.5 - 2.5 hours.

[0053] Specifically, by immersing the support membrane in an ethanol solution, rinsing it with deionized water, and air-drying it dust-free, surface oil, impurities, etc. can be effectively removed, providing a clean surface for subsequent processing. Oxygen plasma treatment introduces polar groups such as hydroxyl and carboxyl groups on the surface of the support membrane, improving surface activity. Immersion treatment with 3-aminopropyltriethoxysilane solution, soaking and drying at room temperature, can form a silane coupling agent coating on the surface of the support membrane, enhancing the bonding force between the membrane surface and the subsequent polymer layer, solving the problems that impurities on the surface of the support membrane affect subsequent processing, low surface activity, and poor bonding with the polymer layer, and effectively improving the compatibility and bonding strength between the support membrane and the subsequent prepared separation layer.

[0054] In S2, according to the molar ratio of carboxymethyl chitosan to piperazine of 1.5 - 2.5:2.5 - 3.5, stir at 250 - 350 r / min until completely dissolved, prepare an aqueous mixed solution with a mass fraction of 2.5% - 3.5% and let it stand for 25 - 35 minutes. Trimellitic acid chloride is dissolved in n-hexane and stirred at 180 - 220 r / min for 0.8 - 1.2 hours to prepare an organic phase solution with a mass fraction of 0.8% - 1.2%.

[0055] Specifically, by precisely controlling the molar ratio of carboxymethyl chitosan to piperazine at 1.5 - 2.5:2.5 - 3.5, stirring at 250 - 350 r / min to prepare an aqueous mixed solution with a mass fraction of 2.5% - 3.5% and letting it stand, so that the two are fully dissolved and mixed evenly, forming a stable reaction system. Dissolve trimellitic acid chloride in n-hexane and stir at 180 - 220 r / min for 0.8 - 1.2 hours to prepare an organic phase solution with a mass fraction of 0.8% - 1.2%, ensuring the uniformity and stability of the organic phase, and ensuring that the aqueous mixed solution and the organic phase solution have appropriate reaction activity and uniformity, solving the problems of insufficient polymerization reaction and unstable membrane structure caused by uneven solution mixing and improper concentration, thus facilitating the formation of a gas separation composite membrane with a uniform structure and excellent performance.

[0056] In S3, the pore size of ZSM-5 molecular sieve is 4 - 12 nm. Add it to the aqueous mixed solution according to the mass ratio of 0.8 - 1.2:5 to carboxymethyl chitosan and continue to stir for 25 - 35 minutes to form a reaction system.

[0057] Specifically, ZSM-5 molecular sieve with a pore size of 4-12 nm is selected and added to the aqueous mixed solution in a mass ratio of 0.8-1.2:5 to carboxymethyl chitosan, and continuously stirred for 25-35 minutes. By utilizing the specific nanoscale pore size and reasonable addition ratio of the molecular sieve, it is uniformly dispersed in the aqueous solution to form a stable reaction system. In this process, the molecular sieve acts as a template, which can guide the formation of nanostructures during the subsequent polymerization reaction, precisely regulate the pore size and distribution of the composite membrane, and solve the problems of difficult control of the pore structure of the composite membrane and poor gas separation selectivity. Through the introduction and uniform dispersion of the molecular sieve template, the gas separation ability and separation efficiency of the gas separation composite membrane for different gases are improved.

[0058] In S4, pour the organic phase solution prepared in step S2, soak for 4-6 minutes, pour off the excess solution, and blot the residue with filter paper. Pour the aqueous phase solution formed in step S3 onto the surface of the support membrane, and carry out an interfacial in-situ polymerization reaction at a temperature of 23-27 °C for 18-22 minutes.

[0059] Specifically, soaking the pretreated support membrane with the organic phase solution prepared in step S2 for 4-6 minutes can enable the organic phase to fully adhere to the surface of the support membrane. Pour off the excess solution and blot the residue to avoid the influence of solution accumulation on the polymerization effect. Subsequently, pour the aqueous phase solution formed in step S3 onto the surface of the support membrane, and carry out an interfacial in-situ polymerization reaction at a temperature of 23-27 °C for 18-22 minutes, so that the organic phase and the aqueous phase fully contact and polymerize on the surface of the support membrane, forming a separation layer with uniform thickness and dense structure, effectively improving the separation performance and mechanical strength of the gas separation composite membrane, and ensuring the efficient separation of gases by the composite membrane.

[0060] In S5, the muffle furnace is heated to 530-570 °C at a rate of 4-6 °C / min and calcined for 5-7 hours to remove the ZSM-5 molecular sieve template, and nitrogen is continuously introduced for protection during the process.

[0061] Specifically, by controlling the muffle furnace to heat up to 530-570 °C at a rate of 4-6 °C / min and maintaining the calcination for 5-7 hours, the ZSM-5 molecular sieve decomposes or volatilizes at high temperature, thereby precisely removing the template in the composite membrane. Nitrogen is continuously introduced for protection during the process, which can prevent the composite membrane from being oxidized or reacting with other components in the air at high temperature, and solve the problem that the template residue affects the gas separation performance and membrane structure stability of the composite membrane. By precisely controlling the heating rate, calcination temperature and time, combined with nitrogen protection, it is ensured that while completely removing the template, the nanoscale pore structure and mechanical properties of the composite membrane are retained to the greatest extent, and the gas separation efficiency and service life of the composite membrane are improved.

[0062] In S6, the temperature of the vacuum drying oven is 75 - 85 °C, the vacuum degree is -0.07 MPa to -0.09 MPa, and it lasts for 3.5 - 4.5 hours to complete the heat annealing treatment. The mass fraction of the glutaraldehyde aqueous solution is 0.8% - 1.2%, and crosslinking is carried out at room temperature for 1.8 - 2.2 hours. After crosslinking, it is rinsed with deionized water 2 - 4 times, each time for 8 - 12 minutes, and finally placed in a vacuum drying oven at 45 - 55 °C to dry for 1.8 - 2.2 hours.

[0063] Specifically, the heat annealing treatment is carried out by setting the temperature of the vacuum drying oven at 75 - 85 °C, the vacuum degree at -0.07 MPa to -0.09 MPa and lasting for 3.5 - 4.5 hours, which promotes the rearrangement of molecular chain segments inside the composite membrane, eliminates internal stress, and improves the denseness and stability of the membrane. The glutaraldehyde aqueous solution with a mass fraction of 0.8% - 1.2% is used for crosslinking at room temperature for 1.8 - 2.2 hours. The glutaraldehyde molecules react chemically with the membrane material molecules to form a crosslinked network structure, enhancing the mechanical strength of the membrane. After crosslinking, it is rinsed with deionized water multiple times, which can effectively remove the unreacted glutaraldehyde and impurities. Finally, it is dried in a vacuum drying oven at 45 - 55 °C for 1.8 - 2.2 hours to further remove moisture and consolidate the crosslinked structure, solving the problems of loose internal structure, insufficient mechanical properties, and impurity residues of the composite membrane, improving the mechanical strength, chemical stability, and structural integrity of the composite membrane, and ensuring its long-term stable performance in gas separation applications.

[0064] In S7, the solid content in the polyimide solution is 4.5% - 5.5%. When spin-coating is carried out by the spin-coating method, it is spin-coated at a speed of 900 - 1100 r / min for 25 - 35 seconds to form a coating with a thickness of about 0.4 - 0.6 μm. The coated composite membrane is placed in a drying oven at 75 - 85 °C to dry for 0.8 - 1.2 hours. Then the composite membrane is placed in a plasma treatment device, and carbon tetrafluoride gas with a flow rate of 25 - 35 sccm is introduced. The reaction chamber pressure is set at 13 - 17 Pa and the power is 75 - 85 W, and it is treated for 7 - 9 minutes to introduce functional groups.

[0065] Specifically, a polyimide solution with a solid content of 4.5%-5.5% is used and spin-coated at a speed of 900-1100 r / min for 25-35 seconds, which can form a coating with a uniform thickness of about 0.4-0.6 μm on the surface of the composite membrane. This coating can fill the microscopic defects on the membrane surface, optimize the smoothness and denseness of the membrane surface. The coated composite membrane is dried at 75-85 °C for 0.8-1.2 hours to fully cure the polyimide coating and enhance the bonding force with the composite membrane. Subsequently, the composite membrane is placed in a plasma treatment device, and carbon tetrafluoride gas with a flow rate of 25-35 sccm is introduced, and it is treated for 7-9 minutes under the conditions of a pressure of 13-17 Pa and a power of 75-85 W. The high energy of the plasma is used to decompose the carbon tetrafluoride gas, and fluorine-containing functional groups are introduced on the surface of the composite membrane, solving the problems of poor gas permeation selectivity and unsatisfactory surface chemical properties caused by surface defects of the composite membrane, and effectively improving the gas separation selectivity, anti-pollution performance and chemical stability of the composite membrane.

[0066] In S1, after the support membrane is soaked and treated with 3-aminopropyltriethoxysilane solution, the surface roughness of the support membrane is detected. If the surface roughness Ra does not meet 0.5-5 nanometers, the soaking treatment with 3-aminopropyltriethoxysilane solution is repeated.

[0067] Specifically, after the support membrane is soaked and treated with 3-aminopropyltriethoxysilane solution, the surface roughness Ra of the support membrane is detected. By setting a standard range of 0.5-5 nanometers, the surface state of the support membrane can be quantitatively evaluated. If the surface roughness does not meet the requirements, the soaking treatment with the silane solution is repeated, which can further cover and modify the surface of the support membrane with the silane coupling agent, adjust the surface microstructure, ensure that the surface roughness of the support membrane is in a suitable range, thereby enhancing the bonding force between the support membrane and the subsequent formed separation layer, and ensuring the stability of the overall structure and the reliability of the performance of the gas separation composite membrane.

[0068] In S7, after the functional groups are introduced by plasma treatment, X-ray photoelectron spectroscopy analysis is performed on the surface of the composite membrane to detect the content and distribution of the functional groups, ensuring that the atomic percentage content of fluorine element on the surface of the composite membrane is 5%-15%, and the deviation of the distribution uniformity of the fluorine-containing groups on the membrane surface is less than 10%.

[0069] Specifically, after the functional groups are introduced by plasma treatment, the surface of the composite membrane is detected by X-ray photoelectron spectroscopy analysis. By measuring the atomic percentage content of fluorine element on the surface of the composite membrane, the introduction effect of the functional groups can be quantitatively evaluated, and the problems of insufficient content or uneven distribution of the functional groups can be found in time, thereby improving the selectivity and separation efficiency of the composite membrane for gases, and enhancing its stability and reliability in gas separation applications.

[0070] Example 1

[0071] Support membrane pretreatment: Select a polysulfone support membrane, soak it in an ethanol solution for 20 minutes, then rinse it twice with deionized water for 3 minutes each time, and then air-dry it in a dust-free environment for 0.5 hour; Place the cleaned support membrane in the reaction chamber, set the oxygen flow rate to 40 sccm, the pressure to 8 Pa, and the power to 80 W, and perform oxygen plasma treatment for 8 minutes; Subsequently, soak the support membrane in a 1.5% (by mass) 3-aminopropyltriethoxysilane solution (volume ratio of anhydrous ethanol to deionized water is 3:1), soak it at room temperature for 1.5 hours, take it out and rinse it twice with anhydrous ethanol, and dry it in a vacuum drying oven at 55 °C for 1.5 hours;

[0072] Solution preparation: Add carboxymethyl chitosan and piperazine to deionized water, at a molar ratio of 1.5:2.5, stir at 250 r / min until completely dissolved, make a 2.5% (by mass) aqueous mixed solution and let it stand for 25 minutes; Dissolve trimesoyl chloride in n-hexane, stir at 180 r / min for 0.8 hour to make a 0.8% (by mass) organic solution;

[0073] Reaction system construction: Select ZSM-5 molecular sieve with a pore size of 4 nm, add the aqueous mixed solution according to the mass ratio of 0.8:5 to carboxymethyl chitosan, and continue to stir for 25 minutes to form a reaction system containing an aqueous phase and an organic phase;

[0074] In-situ polymerization reaction: Lay the support membrane pretreated in step S1 flat in a petri dish, pour the organic phase solution prepared in step S2 to soak for 4 minutes, pour off the excess solution, and blot the residue with filter paper. Then pour the aqueous phase solution formed in step S3 on the surface of the support membrane, and carry out an interfacial in-situ polymerization reaction at a temperature of 23 °C for 18 minutes;

[0075] Template removal: Put the preliminary composite membrane obtained in step S4 into a muffle furnace, heat it up to 530 °C at a rate of 4 °C / min, calcine it for 5 hours to remove the ZSM-5 molecular sieve template, continuously introduce nitrogen for protection during the process, and take it out after natural cooling;

[0076] Post-treatment: Put the preliminary composite membrane treated in step S5 into a vacuum drying oven at a temperature of 75 °C and a vacuum degree of -0.07 MPa, and complete the thermal annealing treatment for 3.5 hours; Soak it in a 0.8% (by mass) aqueous glutaraldehyde solution at room temperature for crosslinking for 1.8 hours. After crosslinking, rinse it twice with deionized water for 8 minutes each time, and finally put it into a vacuum drying oven at 45 °C to dry for 1.8 hours;

[0077] Surface optimization: A polyimide solution with a solid content of 4.5% was dropped at the center of the composite film after being treated in step S6, and spin-coated at a speed of 900 r / min for 25 seconds to form a coating; the coated composite film was placed in a drying oven at 75 °C and dried for 0.8 hours, and then placed in a plasma treatment device. Tetrafluoromethane gas with a flow rate of 25 sccm was introduced, the reaction chamber pressure was set to 13 Pa, the power was 75 W, and the treatment was carried out for 7 minutes to introduce functional groups.

[0078] Example 2

[0079] Support membrane pretreatment: A polysulfone support membrane was selected, soaked in an ethanol solution for 30 minutes, then rinsed with deionized water 3 times, 5 minutes each time, and then air-dried in a dust-free environment for 1 hour; the cleaned support membrane was placed in the reaction chamber, the oxygen flow rate was set to 50 sccm, the pressure was 10 Pa, the power was 100 W, and oxygen plasma treatment was carried out for 10 minutes; subsequently, the support membrane was soaked in a 2% (by mass) 3-aminopropyltriethoxysilane solution (volume ratio of absolute ethanol to deionized water 4:1) at room temperature for 2 hours, taken out, rinsed with absolute ethanol 3 times, and dried in a vacuum drying oven at 60 °C for 2 hours;

[0080] Solution preparation: Carboxymethyl chitosan and piperazine were added to deionized water, and stirred at a molar ratio of 2:3 at 300 r / min until completely dissolved to prepare an aqueous mixed solution with a mass fraction of 3% and allowed to stand for 30 minutes; trimellitic acid chloride was dissolved in n-hexane and stirred at 200 r / min for 1 hour to prepare an organic solution with a mass fraction of 1%;

[0081] Reaction system construction: ZSM-5 molecular sieve with a pore size of 8 nm was selected, and the aqueous mixed solution was added according to the mass ratio of 1:5 to carboxymethyl chitosan, and stirring was continued for 30 minutes to form a reaction system containing an aqueous phase and an organic phase;

[0082] In-situ polymerization reaction: The support membrane pretreated in step S1 was laid flat in a petri dish, the organic phase solution prepared in step S2 was poured in and infiltrated for 5 minutes, the excess solution was poured off, and the residue was blotted dry with filter paper. Then the aqueous phase solution formed in step S3 was poured on the surface of the support membrane, and an interfacial in-situ polymerization reaction was carried out at a temperature of 25 °C for 20 minutes;

[0083] Template removal: The preliminary composite membrane obtained in step S4 was placed in a muffle furnace, heated to 550 °C at a rate of 5 °C / min, calcined for 6 hours to remove the ZSM-5 molecular sieve template, and nitrogen was continuously introduced for protection during the process, and then taken out after natural cooling;

[0084] Post-treatment: Place the preliminary composite film after the treatment in step S5 into a vacuum drying oven at a temperature of 80°C and a vacuum degree of -0.08 MPa for 4 hours to complete the thermal annealing treatment; soak it in an aqueous solution of glutaraldehyde with a mass fraction of 1% at room temperature for 2 hours. After crosslinking, rinse it 3 times with deionized water, 10 minutes each time, and finally place it in a vacuum drying oven at 50°C to dry for 2 hours.

[0085] Surface optimization: Drop a polyimide solution with a solid content of 5% at the center of the composite film after the treatment in step S6, and spin-coat it at a speed of 1000 r / min for 30 seconds using the spin-coating method to form a coating; place the coated composite film in a drying oven at 80°C to dry for 1 hour, and then put it into a plasma treatment device. Introduce carbon tetrafluoride gas with a flow rate of 30 sccm, set the reaction chamber pressure to 15 Pa and the power to 80 W, and treat it for 8 minutes to introduce functional groups.

[0086] Example 3

[0087] Pretreatment of the support membrane: Select a polysulfone support membrane, soak it in an ethanol solution for 40 minutes, then rinse it 4 times with deionized water, 7 minutes each time, and then air-dry it in a dust-free environment for 1.5 hours; place the cleaned support membrane in the reaction chamber, set the oxygen flow rate to 60 sccm, the pressure to 12 Pa, and the power to 120 W, and perform oxygen plasma treatment for 12 minutes; then soak the support membrane in a 3-aminopropyltriethoxysilane solution with a mass fraction of 2.5% (volume ratio of anhydrous ethanol to deionized water is 5:1) at room temperature for 2.5 hours. After taking it out, rinse it 4 times with anhydrous ethanol and dry it in a vacuum drying oven at 65°C for 2.5 hours.

[0088] Solution preparation: Add carboxymethyl chitosan and piperazine to deionized water according to a molar ratio of 2.5:3.5, and stir at 350 r / min until completely dissolved to make an aqueous mixed solution with a mass fraction of 3.5% and let it stand for 35 minutes; dissolve trimesoyl chloride in n-hexane and stir at 220 r / min for 1.2 hours to make an organic solution with a mass fraction of 1.2%.

[0089] Reaction system construction: Select ZSM-5 molecular sieve with a pore size of 12 nm, add the aqueous mixed solution according to a mass ratio of 1.2:5 to carboxymethyl chitosan, and continue to stir for 35 minutes to form a reaction system containing an aqueous phase and an organic phase.

[0090] In-situ polymerization reaction: Lay the support membrane pretreated in step S1 flat in a petri dish, pour the organic phase solution prepared in step S2 to soak for 6 minutes, pour off the excess solution, and blot the residue with filter paper. Then pour the aqueous phase solution formed in step S3 on the surface of the support membrane and carry out an interfacial in-situ polymerization reaction at a temperature of 27°C for 22 minutes.

[0091] Template removal: Put the preliminary composite membrane obtained in step S4 into a muffle furnace, heat it up to 570 °C at a rate of 6 °C / min, calcine for 7 hours to remove the ZSM-5 molecular sieve template, continuously introduce nitrogen for protection during the process, and take it out after natural cooling;

[0092] Post-treatment: Put the preliminary composite membrane treated in step S5 into a vacuum drying oven at a temperature of 85 °C and a vacuum degree of -0.09 MPa, and complete the heat annealing treatment for 4.5 hours; Immerse it in an aqueous solution of glutaraldehyde with a mass fraction of 1.2% at room temperature for cross-linking for 2.2 hours. After the cross-linking is completed, rinse it 4 times with deionized water, 12 minutes each time, and finally put it into a vacuum drying oven at 55 °C to dry for 2.2 hours;

[0093] Surface optimization: Drop a polyimide solution with a solid content of 5.5% at the center of the composite membrane treated in step S6, and spin-coat it at a speed of 1100 r / min for 35 seconds by the spin-coating method to form a coating; Put the coated composite membrane into a drying oven at 85 °C to dry for 1.2 hours, and then put it into a plasma treatment device, introduce carbon tetrafluoride gas with a flow rate of 35 sccm, set the reaction chamber pressure to 17 Pa and the power to 85 W, and treat for 9 minutes to introduce functional groups.

[0094] Control example

[0095] Simply clean the polysulfone support membrane; When preparing the solution, dissolve polysulfone in N-methylpyrrolidone to make a casting solution with a mass fraction of 20%, stir until completely dissolved, and then let it stand for defoaming.

[0096] Experimental table

[0097]

[0098] Gas permeability (Barrer): It is an index to measure the rate of gas passing through the membrane. The larger the value, the more gas passes through the membrane per unit area per unit time under certain conditions, that is, the stronger the gas transmission ability of the membrane;

[0099] Gas selectivity (CO2 / CH4): It is a parameter used to characterize the gas separation ability of the membrane. Taking carbon dioxide (CO2) and methane (CH4) as examples, this ratio is the ratio of CO2 permeability to CH4 permeability under the same conditions. The higher the ratio, the better the separation effect of the membrane on CO2 and CH4, and the more effectively the separation of the two can be achieved;

[0100] Tensile strength (MPa): It refers to the maximum stress that the membrane can withstand before tensile fracture, with the unit of megapascal (MPa), which reflects the tensile resistance ability of the membrane. The higher the tensile strength, the stronger the ability of the membrane to resist external tensile force without breaking during use, reflecting the mechanical stability of the membrane;

[0101] Elongation at break (%):It represents the percentage of the length by which the film elongates when stretched to break, compared to its initial length. It measures the flexibility and ductility of the film. The larger the elongation at break, the greater the degree of deformation the film can undergo during stretching without breaking, reflecting the toughness of the film.

[0102] Film surface roughness Ra (nm): It is a parameter used to quantify the unevenness of the microscopic geometry of the film surface, with the unit of nanometer (nm). The Ra value represents the arithmetic mean deviation of the profile, that is, the arithmetic mean of the absolute values of the profile offsets within the sampling length. The smaller the Ra value, the smoother the film surface. Conversely, the larger the Ra value, the rougher the film surface, which will affect the interaction between the film and the gas and the separation performance of the film, etc.

[0103] Based on the data in the above experimental table, the method for preparing a gas separation composite membrane by adding carboxymethyl chitosan polymerization has improved the gas permeability, enhanced the separation effect, strengthened the mechanical stability, increased the toughness of the membrane, and reduced the surface roughness.

[0104] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan, characterized in that, It includes the following steps: S1. Support membrane pretreatment: successively perform cleaning treatment, oxygen plasma treatment, and immersion treatment in 3-aminopropyltriethoxysilane solution on a polysulfone, polyethersulfone, or polyacrylonitrile support membrane; S2. Solution preparation: Prepare deionized water, carboxymethyl chitosan, piperazine, trimesoyl chloride, and n-hexane. Add carboxymethyl chitosan and piperazine to deionized water, stir until completely dissolved, make an aqueous phase mixed solution and let it stand. Dissolve trimesoyl chloride in n-hexane and stir to make an organic phase solution; S3. Reaction system construction: Select ZSM-5 molecular sieve as a template and add it to the aqueous phase mixed solution. After stirring, form a reaction system containing an aqueous phase and an organic phase; S4. In-situ polymerization reaction: Lay the support membrane pretreated in step S1 flat in a petri dish, pour in the organic phase solution prepared in step S2 to infiltrate, and then pour the aqueous phase solution formed in step S3 on the surface of the support membrane to carry out an interfacial in-situ polymerization reaction; S5. Template removal: Put the preliminary composite membrane obtained in step S4 into a muffle furnace for calcination to remove the ZSM-5 molecular sieve template, and take it out after natural cooling; S6. Put the preliminary composite membrane treated in step S5 into a vacuum drying oven for heat annealing treatment, soak it in an aqueous glutaraldehyde solution at room temperature for crosslinking, then rinse it with deionized water, and finally dry it; S7. Surface optimization: Drop polyimide solution at the center of the composite membrane treated in step S6, then put it into a drying oven for drying, and finally put it into a plasma device for treatment.

2. The method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S1, the cleaning treatment includes soaking the support membrane in an ethanol solution for 20 - 40 minutes, then rinsing it with deionized water 2 - 4 times, 3 - 7 minutes each time, and then air-drying it in a dust-free environment for 0.5 - 1.5 hours. The oxygen plasma treatment includes setting the oxygen flow rate at 40 - 60 sccm, the pressure at 8 - 12 Pa, and the power at 80 - 120 W in the reaction chamber for the cleaned support membrane, and treating it for 8 - 12 minutes. The 3-aminopropyltriethoxysilane solution immersion treatment includes soaking the support membrane in a 3-aminopropyltriethoxysilane solution with a mass fraction of 1.5% - 2.5%. The 3-aminopropyltriethoxysilane solution is a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1 - 5:1, soak it at room temperature for 1.5 - 2.5 hours, take it out and rinse it with anhydrous ethanol 2 - 4 times, and dry it in a vacuum drying oven at 55 - 65 °C for 1.5 - 2.5 hours.

3. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S2, according to the molar ratio of carboxymethyl chitosan to piperazine of 1.5 - 2.5:2.5 - 3.5, stir at 250 - 350 r / min until completely dissolved, make an aqueous phase mixed solution with a mass fraction of 2.5% - 3.5% and let it stand for 25 - 35 minutes. Dissolve trimesoyl chloride in n-hexane and stir at 180 - 220 r / min for 0.8 - 1.2 hours to make an organic phase solution with a mass fraction of 0.8% - 1.2%.

4. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S3, the pore diameter of the ZSM-5 molecular sieve is 4 - 12 nm, add it to the aqueous phase mixed solution according to the mass ratio of 0.8 - 1.2:5 to carboxymethyl chitosan, and continue to stir for 25 - 35 minutes to form a reaction system.

5. A method for preparing a gas separation composite membrane by adding carboxymethyl chitosan polymerization according to claim 1, characterized in that, In S4, pour in the organic phase solution prepared in step S2, soak for 4 - 6 minutes, pour off the excess solution, and blot dry the residue with filter paper. Then pour the aqueous phase solution formed in step S3 onto the surface of the support membrane, and carry out an interfacial in-situ polymerization reaction at a temperature of 23 - 27 °C for 18 - 22 minutes.

6. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S5, the muffle furnace is heated to 530 - 570 °C at a rate of 4 - 6 °C / min and calcined for 5 - 7 hours to remove the ZSM-5 molecular sieve template, and nitrogen is continuously introduced for protection during the process.

7. A method for preparing a gas separation composite membrane by adding carboxymethyl chitosan polymerization according to claim 1, characterized in that, In S6, the temperature of the vacuum drying oven is 75 - 85 °C, the vacuum degree is -0.07 MPa - -0.09 MPa, and it lasts for 3.5 - 4.5 hours to complete the thermal annealing treatment. The mass fraction of the glutaraldehyde aqueous solution is 0.8% - 1.2%, and crosslinking is carried out at room temperature for 1.8 - 2.2 hours. After crosslinking, it is rinsed with deionized water 2 - 4 times, each time for 8 - 12 minutes, and finally dried in a vacuum drying oven at 45 - 55 °C for 1.8 - 2.2 hours.

8. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S7, the solid content in the polyimide solution is 4.5% - 5.5%. When spin-coating is carried out by the spin-coating method, it is spin-coated at a speed of 900 - 1100 r / min for 25 - 35 seconds to form a coating with a thickness of about 0.4 - 0.6 μm. The coated composite membrane is placed in a drying oven at 75 - 85 °C and dried for 0.8 - 1.2 hours. Then the composite membrane is placed in a plasma treatment device, and carbon tetrafluoride gas with a flow rate of 25 - 35 sccm is introduced. The pressure of the reaction chamber is set to 13 - 17 Pa and the power is 75 - 85 W, and it is treated for 7 - 9 minutes to introduce functional groups.

9. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S1, after the support membrane is soaked and treated with 3-aminopropyltriethoxysilane solution, the surface roughness of the support membrane is detected. If the surface roughness Ra does not meet 0.5 - 5 nanometers, repeat the soaking treatment with 3-aminopropyltriethoxysilane solution.

10. A method for preparing a gas separation composite membrane by adding and polymerizing carboxymethyl chitosan according to claim 1, characterized in that, In S7, after the functional groups are introduced by plasma treatment, X-ray photoelectron spectroscopy analysis is carried out on the surface of the composite membrane to detect the content and distribution of the functional groups, ensuring that the atomic percentage content of fluorine elements on the surface of the composite membrane is 5% - 15%, and the uniformity deviation of the distribution of fluorine-containing groups on the membrane surface is less than 10%.